1990
DOI: 10.1093/ptj/70.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Voltage Pulsed Direct Current on Edema Formation Following Impact Injury

Abstract: Edema results in pain and may lead to reduced functional mobility. High voltage pulsed direct current (HVPC) has recently been advocated for edema control. The purpose of our study was to determine the effect of HVPC on edema formation in frogs. Hind limbs of 20 anesthetized frogs were injured by dropping a 450-g weight onto the plantar aspects of the feet. One hind limb of each frog was randomly selected to receive continuous 120-Hz HVPC at voltages 10% lower than those needed to evoke muscle contraction. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 5 publications
1
30
0
2
Order By: Relevance
“…These results agree with previous animal studies 7,8,10,11,25,27 that showed the effectiveness of HVPC(-) in the treatment of posttraumatic edema.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results agree with previous animal studies 7,8,10,11,25,27 that showed the effectiveness of HVPC(-) in the treatment of posttraumatic edema.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in edema using this intensity has been shown in several animal studies 7,8,[10][11]25,27,28 . Another study used a current at motor threshold in the treatment of ankle sprain (acute phase) in humans and found no difference between the treatment group and the CG 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical advantage of HVES is that the stimulation is confortable and affects sensory, motor and nociceptive nerve fibers. The physical parameters involved in this current allow for several therapeutic effects, such as pain and edema control 22 , as well as acceleration of tissue repair 23,24 .…”
Section: Discussionmentioning
confidence: 99%